PERLINDNGAN HUKUM TERHADAP KESELAMATAN KERJA WANITA PADA USAHA HIBURAN MALAM DI KOTA PALU - Maisa Maisa (Fakultas Hukum Universitas Muhammadiyah Palu, 2017)
The main issue discussed in this thesis is how the implementation of legal protection for the safety of women on night entertainment business. This study uses the type of normative legal research to answer the proposed problem formulation. The results of the study indicate that the implementation of legal protection for the safety of women in the night business which includes: 1. Work permit for women; 2. Providing nutritious food and drink; 3. Transportation; 4. Lighting at work place at night; 5. Protection of crime, safety and morals; Already implemented by entrepreneurs, although in terms of nourishing food and beverages and transportation, entrepreneurs are replaced with money because the company can not provide such facilities on a daily basis.Keywords : Legal protection, Women's Occupational Safety, Night Business